The CDH1 -160C/A polymorphism is associated with breast cancer: evidence from a meta-analysis. Issue 1 (December 2016) - Ma, Ying-Yu; Wu, Wei-Quan; Liu, Zheng-Chuang; Yu, Xiao-Fen; Guo, Kun; He, Qi-Wen; Jiang, Shi-Bin; Shao, Qin-Shu; Tao, Hou-Quan; Huang, Dong-Sheng
Abstract Background Numerous epidemiological studies have evaluated the association between the CDH1 -160C/A polymorphism and the risk of breast cancers. However, these studies have yielded conflicting results. To derive a more precise estimation of this association, this meta-analysis was conducted. Methods A comprehensive search using the keywords "CDH1, " "E-Cadherin, " "polymorphism, " "SNP, " and "variant" combined with "breast, " "cancer, " "tumor, " or "carcinomas" was conducted. Pooled odds ratios (ORs) with 95 % confidence intervals (CIs) were appropriately calculated using a fixed effect or random effect model. Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) 2009 checklist was used for this meta-analysis. Results Four publications including five studies were identified. It was found that the CDH1 -160C/A polymorphism was significantly associated with breast cancer risk in the dominant model (CA + AA vs. CC: OR = 1.207, 95 % CI = 1.031–1.412, P  = 0.019). Conclusions Our meta-analysis demonstrated that the -160C/A polymorphism in the CDH1 gene might contribute to breast cancer susceptibility. Further investigations using a much larger sample including different ethnicities are still needed to verify this association.